The contact theorem and sum rules in the theory of electrical double layer - Holovko, M.F.; Badiali, J.P. (Condensed Matter Physics, 2005)
The specific sum rules in the theory of electrical double layer are formulated as the consequence of contact theorem. They concern the correlation functions of electrolyte when one ion is located on the surface. A simple interpretation of the obtained relations is given.